How Power Distance Interacts with Culture and Status to Explain Intra‐ and Intercultural Negotiation Behaviors: A Multilevel Analysis. (17th October 2018) - Liu, Meina
Abstract: This study examines how culture and status qualify the effects of power distance (PD) values on bargaining tactics in intra‐ and intercultural negotiations, as well as Chinese and American negotiators' behavioral difference in these contexts. Data were collected from 34 intercultural dyads, 32 American dyads, and 35 Chinese dyads that completed job offer negotiations. Results showed substantial contextual variations in the actor and partner effects of PD values. Whereas Chinese employees' PD values positively influenced American managers' priority information exchange, American employees' PD values had a negative partner effect on it. Whereas Chinese employees' PD values negatively influenced Chinese managers' relationship building, American employees' PD values had a positive partner effect on it. American managers and employees both used significantly fewer integrative tactics and more distributive tactics in intercultural than intracultural negotiations, but neither Chinese managers nor Chinese employees exhibited behavioral difference. Theoretical and practical implications of the study are discussed.